Calcium binding and voltage gating in Cx46 hemichannels. Issue 1 (December 2017) - Pinto, Bernardo; Pupo, Amaury; García, Isaac; Mena-Ulecia, Karel; Martínez, Agustín; Latorre, Ramón; Gonzalez, Carlos
Abstract The opening of connexin (Cx) hemichannels in the membrane is tightly regulated by calcium (Ca2+ ) and membrane voltage. Electrophysiological and atomic force microscopy experiments indicate that Ca2+ stabilizes the hemichannel closed state. However, structural data show that Ca2+ binding induces an electrostatic seal preventing ion transport without significant structural rearrangements. In agreement with the closed-state stabilization hypothesis, we found that the apparent Ca2+ sensitivity is increased as the voltage is made more negative. Moreover, the voltage and Ca2+ dependence of the channel kinetics indicate that the voltage sensor movement and Ca2+ binding are allosterically coupled. An allosteric kinetic model in which the Ca2+ decreases the energy necessary to deactivate the voltage sensor reproduces the effects of Ca2+ and voltage in Cx46 hemichannels. In agreement with the model and suggesting a conformational change that narrows the pore, Ca2+ inhibits the water flux through Cx hemichannels. We conclude that Ca2+ and voltage act allosterically to stabilize the closed conformation of Cx46 hemichannels.